Human ontological vulnerability - Gcelu, Awongwa (Rhodes University, 2026)
South Africa's brutal history of colonialism and apartheid has threatened the survival of the country's indigenous cultural identities and ways of being. The American philosopher Jonathan Lear explains that all cultural groups live with what he terms "ontological vulnerability" – the possibility that a group's cultural identity and ways of being might become devastated. In this thesis, I argue that in post-apartheid South Africa, the mainstream society continues to create conditions that threaten the cultural integrity of AmaXhosa. I demonstrate that members of the AmaXhosa cultural group face an impossible choice to either participate in the country's mainstream society or maintain their traditional ways of being, without the option to integrate both meaningfully. The cultural ways of being of AmaXhosa are not adequately recognised or accommodated within South Africa's mainstream society. To substantiate this argument, I will present three cases where significant cultural practices of AmaXhosa are marginalised and forced to deteriorate by the pressures of mainstream South African society. Through an analysis of these practices, I conclude that South African society undermines AmaXhosa cultural identity and traditions, steering their heritage toward erosion. AmaXhosa people face a dilemma to either maintain their cultural practices and risk economic marginalisation or participate in mainstream society by adopting Eurocentric values and behaviours – a prerequisite for meaningful social and economic inclusion. Confronted with this hostile environment, most AmaXhosa choose mainstream participation, which results in alienation from their cultural roots and abandonment of cultural AmaXhosa ways of being. To address the ontological vulnerability of AmaXhosa people, the South African society must redirect the trajectory of AmaXhosa culture from potential cultural devastation toward meaningful participation in the country's mainstream society. This transformation requires adjustments from both the AmaXhosa cultural group and the dominant mainstream South African society. The AmaXhosa community needs to engage with modernity while recognising that modernity is not synonymous with Westernisation, Eurocentrism, or forced acculturation. Rather, changing natural and social conditions define the evolving living circumstances of human communities. For cultural survival and vitality, AmaXhosa traditions must adapt to contemporary realities while preserving core cultural values and perspectives. Simultaneously, mainstream South African society must acknowledge and embrace multiple conceptual frameworks and worldviews that can contribute to improving living conditions for all citizens. This requires developing a genuinely multicultural social framework that values diverse knowledge systems and cultural practices. The integration of these complementary adjustments would help AmaXhosa and other marginalised cultural groups to find a balanced path between a nostalgic attachment to the past and an uncritical acceptance of Western cultural models. This balanced approach offers the possibility of cultural renewal and meaningful participation in a diverse South African society.
culture and identity decay in the face of cultural devastation
Keywords: Culture (http://id.loc.gov/authorities/subjects/sh85034755); Group identity (http://id.loc.gov/authorities/subjects/sh85057485); Cultural identity (https://www.wikidata.org/wiki/Q1368367)